2019
DOI: 10.1002/ijc.32663
|View full text |Cite
|
Sign up to set email alerts
|

In vitro elimination of epidermal growth factor receptor‐overexpressing cancer cells by CD32A‐chimeric receptor T cells in combination with cetuximab or panitumumab

Abstract: Cetuximab and panitumumab bind the human epidermal growth factor receptor (EGFR). Although the chimeric cetuximab (IgG1) triggers antibody‐dependent‐cellular‐cytotoxicity (ADCC) of EGFR positive target cells, panitumumab (a human IgG2) does not. The inability of panitumumab to trigger ADCC reflects the poor binding affinity of human IgG2 Fc for the FcγRIII (CD16) on natural killer (NK) cells. However, both human IgG1 and IgG2 bind the FcγRII (CD32A) to a similar extent. Our study compares the ability of T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 27 publications
(50 reference statements)
2
41
0
Order By: Relevance
“…Since in vitro and in vivo studies have demonstrated the efficacy of CAR-T cell therapy against TNBC cells, combination approaches may further expand the therapeutic opportunities in the future. In fact, CD32A 131R –chimeric receptor (CR) T cells in combination with cetuximab or panitumumab resulted in in vitro anticancer activity in TNBC cells [ 447 ]. Cetuximab (IgG1) can induce ADCC- of EGFR-positive cells, whereas panitumumab (IgG2) cannot be due to distinct binding to the different Fc gamma receptors (FcγRs) CD16 and CD32A; IgG2 has low affinity for CD16, while IgG1 and IgG2 bind to CD32A with different affinities [ 598 , 599 ].…”
Section: Combination Strategy For Overcoming Egfri Resistance In Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Since in vitro and in vivo studies have demonstrated the efficacy of CAR-T cell therapy against TNBC cells, combination approaches may further expand the therapeutic opportunities in the future. In fact, CD32A 131R –chimeric receptor (CR) T cells in combination with cetuximab or panitumumab resulted in in vitro anticancer activity in TNBC cells [ 447 ]. Cetuximab (IgG1) can induce ADCC- of EGFR-positive cells, whereas panitumumab (IgG2) cannot be due to distinct binding to the different Fc gamma receptors (FcγRs) CD16 and CD32A; IgG2 has low affinity for CD16, while IgG1 and IgG2 bind to CD32A with different affinities [ 598 , 599 ].…”
Section: Combination Strategy For Overcoming Egfri Resistance In Tnbcmentioning
confidence: 99%
“…Cetuximab (IgG1) can induce ADCC- of EGFR-positive cells, whereas panitumumab (IgG2) cannot be due to distinct binding to the different Fc gamma receptors (FcγRs) CD16 and CD32A; IgG2 has low affinity for CD16, while IgG1 and IgG2 bind to CD32A with different affinities [ 598 , 599 ]. The CD32A 131R -CR T cells were superior to CD16 158F -CR T cells in their antitumor activity against the EGFR-positive TNBC cell line MDA-MB-468 [ 447 ]. The antitumor effects of CD32A 131 -CR T cells in combination with anti-EGFR antibodies were dependent on the level of cell surface EGFR, since this combination does not induce cytotoxicity of MDA-MB-231 cells.…”
Section: Combination Strategy For Overcoming Egfri Resistance In Tnbcmentioning
confidence: 99%
“…Only in combination with tumor-specific monoclonal antibodies (mAb) (e.g., rituximab, trastuzumab, cetuximab), CD16 CAR T cells triggered efficient tumor lysis both in vitro and in vivo (Figure 2a) [27][28][29][30][31]. Due to the low binding affinity of CD16 to human IgG2, Caratelli et al later utilized the CD32A ECD for the construction of adaptor CARs that are able to bind IgG1 and IgG2 with similar affinities [32]. The therapeutic activity of antibodies is clearly determined by their glycosylation pattern [33].…”
Section: Fc-binding Adaptor Carsmentioning
confidence: 99%
“…Contrary to CD16, CD32A has moderate affinity also for IgG2, which is important in the treatment of epidermal growth factor receptor (EGFR)-positive tumors: beside Cetuximab (IgG1), Panitumumab (IgG2) is used as a therapeutic antibody. Directly comparing CD32A CR-to CD16 CR-T cells in combination with both those antibodies in vitro showed superior lytic capacity of the former construct, benefiting from both mAbs directing ADCC, while CD16 can only bind one of them [220].…”
Section: Fcγriia (Cd32a)mentioning
confidence: 98%
“…Based on the emergence of Fcγ CRs using a CD16 extracellular domain, Caratelli et al designed a CD32A131R (low-affinity variant) chimeric receptor with a CD8α TM and a CD28/CD3ζ signaling domain to be retrovirally transduced into peripheral blood T cells [220]. Contrary to CD16, CD32A has moderate affinity also for IgG2, which is important in the treatment of epidermal growth factor receptor (EGFR)-positive tumors: beside Cetuximab (IgG1), Panitumumab (IgG2) is used as a therapeutic antibody.…”
Section: Fcγriia (Cd32a)mentioning
confidence: 99%